PENGARUH ISLAMIC CORPORATE GOVERNANCE, GREEN BANKING DAN LEVERAGE TERHADAP HARGA SAHAM PERBANKAN SYARIAH (UUS) YANG TERDAFTAR DI OJK - Dayanti, Susi; Jayanti, Sri Delasmi; Septiatin, Aziz (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to analyze the influence of Islamic Corporate Governance, Green Banking, and Leverage on the stock price of Islamic banking (Sharia Business Unit/UUS) registered with the Financial Services Authority (OJK). The study uses a quantitative approach with secondary data and panel data regression analysis methods using EViews 12. The results show that partially Islamic Corporate Governance, Green Banking and Leverage do not have a significant effect on stock prices, while, simultaneously, the three variables have a significant effect on the stock price of Islamic banking. This finding indicates that financial factors are still the main consideration for investors, while the implementation of sharia governance and green banking has not been fully reflected in stock price movements.